The complex DNA molecular combination with a linear and circular structure in Magnolia kwangsiensis mitochondrial genome - Li, Qing; Sheng, Wentao (Frontiers in Plant Science, 2025)
BackgroundMagnolia kwangsiensis is an endangered Magnoliaceae species, holding scientific, aesthetic, and economic value. But limited genetic research was reported. To better understand M. kwangsiensis genomics, we aimed to assemble and analyze its mitochondrial genome.ResultsM. kwangsiensis has a branched structure, composing a linear and circular molecular structure with 428,449 bp and 126,869 bp, and GC contents of 47.51% and 47.38%. The total genome size is 555,318 bp, with GC content of 47.47%. A total of 68 genes were annotated, comprising 40 protein-coding, 23 tRNA, three rRNA genes, and two pseudo-genes. And nad1, atp9, and nad6 exhibited the highest nucleotide diversity, while atp1 and nad5 exhibited the lowest. Relative synonymous codon usage (RSCU) analysis revealed 29 codons with RSCU values > 1, showing A/U preference for codons ending. Moreover, 211 simple sequence, 1101 dispersed, and 39 tandem repeats were checked. The mitochondrial genome of M. kwangsiensis and Magnolia figo showed relatively good synteny. And 32 homologous fragments were discriminated between its mitochondrial and chloroplast genome, with a total of 29,253 bp and an average 914 bp. Phylogenetic analysis indicated that M. kwangsiensis is the most closely related to Liriodendron tulipifera.ConclusionThe information provided herein contributes genomic knowledge for the M. kwangsiensis breeding research.